Castlesteads and Langside pit alignments (Scottish Historical and Archaeological Internet Reports, 2010)
The alignment at Castlesteads comprised nine large pits which are technically undated. A nearby cluster of seven pits or postholes produced radiocarbon dates in the Neolithic period. Two isolated pits, a stony spread and rig and furrow were also identified. Prehistoric pottery was recovered from three pits forming the cluster. A single Roman or medieval sherd was redeposited in the upper fill of one of the pits in the alignment. Chipped stone included a microlithic and a flint scraper. The much degraded pollen profile was suggestive of open pasture and an absence of arboreal vegetation. The Langside alignment comprised eight pits and it is suggested that construction began in the early Iron Age. There are specialist reports on lithics, a coarse stone grinder, miscellaneous redeposited finds, charcoal and soil micromorphology. The two sites are compared and the possible purpose of pit alignments is considered.